DWI Combined With Hepatobiliary-Phase Enhanced Imaging Can Better Differentiate Cholangiocarcinoma From Atypical Liver Abscesses - Xing, Li-Hong; Zhuo, Li-Yong; Zhang, Yu; Ma, Xi; Ma, Ze-Peng; Zhao, Ying-Jia; Yin, Xiao-Ping; Gao, Bu-Lang (Frontiers in Oncology, 2022)
Objective: To investigate the value of diffusion-weighted imaging (DWI) combined with the imaging at the hepatobiliary stage of Gd-BOPTA enhancement in differentiating intrahepatic mass-forming cholangiocarcinoma (IMCC) from atypical liver abscess. Materials and Methods: A retrospective analysis was performed on 43 patients with IMCCs and 25 patients with atypical liver abscesses. The DWI signal, the absolute value of the contrast noise ratio (│CNR│) at the hepatobiliary stage, and visibility were analyzed. Results: A relatively high DWI signal and a relatively high peripheral signal were presented in 29 patients (67.5%) in the IMCC group, and a relatively high DWI signal was displayed in 15 patients (60.0%) in the atypical abscess group with only one (6.7%) exhibiting a relatively high peripheral signal and 14 (93.3%, 14/15) showing a relatively high central signal. A significant (P<0.001) difference existed in the proportion of patients presenting with this pattern of signal between the two groups. On T2WI, IMCC was mainly manifested by homogeneous signal (53.5%), whereas atypical liver abscesses were mainly manifested by heterogeneous signal and relatively high central signal (32%, and 64%), with a significant difference (P<0.001) between the two groups. On the hepatobiliary-stage imaging, there was a statistically significant difference in peripheral │CNR│ (P< 0.001) and visibility. The sensitivity of the hepatobiliary-stage imaging was significantly (P=0.002) higher than that of DWI. The sensitivity and accuracy of DWI combined with enhanced hepatobiliary-stage imaging were significantly (P=0.002 and P<0.001) higher than those of either hepatobiliary-stage imaging or DWI alone. Conclusion: IMCCs and atypical liver abscesses exhibit different imaging signals, and combination of DWI and hepatobiliary-stage enhanced imaging has higher sensitivity and accuracy than either technique in differentiating IMCCs from atypical liver abscesses.